Development of chitosan‐polygalacturonic acid polyelectrolyte complex fibrous scaffolds using the hydrothermal treatment for bone tissue engineering. Issue 3 (17th October 2022) - Wasupalli, Geeta Kumari; Verma, Devendra
Abstract: An ideal bone regeneration scaffold system needs to meet the high compressive properties of the bone. The stiffness of the scaffold extracellular matrix determines the cell's fate via cell adhesion migration and differentiation in‐vitro and in‐vivo. This study aims to investigate the effect of hydrothermal treatment on polyelectrolyte complex (PEC) fibrous biomaterials and its effect on scaffold morphology, cell viability, and function in‐vitro. FTIR analysis revealed the ability of the thermal treatment to set the interaction of HAp with polymeric PEC fibers. FESEM analysis showed that with an increase in temperature, the interconnectivity and pore size increased (control—82.38 ± 12.92 μm; at 120°C—335.48 ± 85.10 μm). Mechanical tests showed that the scaffolds heated at 90°C showed the highest stiffness in both dry and wet states (dry state: 1.82 ± 0.07 MPa, wet state: 122 ± 1.78 kPa). Additionally, the hydrothermal treatment also improved the aqueous stability as well as swelling capacity. According to the experimental findings, hydrothermal treatment is a useful technique for crosslinker‐free gelation with improved mechanical strength and nanofibrous structure. Furthermore, the cell adhesion, proliferation, and osteogenic differentiation of the MG63 cells on the hydrogel scaffolds in‐vitro were evaluated by MTT assay, confocal imaging, alkaline phosphatase assay, and collagen estimation. The in‐vitro study showed that scaffolds fabricated at 90°C promoted better MG63 cell attachment, proliferation, and differentiation. These results suggest the potential use of hydrothermal treated chitosan‐polygalacturonic acid (PgA) fibrous scaffolds in bone tissue engineering.